Combined Effects of Smoking and Bilirubin Levels on the Risk of Lung Cancer in Korea: The Severance Cohort Study - Lim, Jung-eun (Public Library of Science, 2014)
BACKGROUND: Smoking is a major risk factor for lung cancer. Bilirubin, an antioxidant, is inversely associated with the risk of diseases related to oxidative stress. This study was conducted to determine the influence of smoking and bilirubin levels on the risk of lung cancer in the Severance cohort study. METHODS: This study included 68,676 Korean who received a health examination at Severance Health Promotion Center from 1994 to 2004. Serum bilirubin measurements within normal range were divided into tertiles whereas smoking states were divided as never-smokers, former smokers and current smokers. A diagnosis of lung cancer was coded as occurring based on the report from the National Cancer Registry. Hazard ratios (HRs) and 95% confidence intervals (95% CIs) were calculated using Cox proportional hazards model. RESULTS: At the end of the study period, 240 patients (men: 181, women: 59) developed lung cancer. Compared to those with bilirubin levels ≥1.0 mg/dL, HRs (95% CI) for lung cancer were 2.8 (1.8–4.2) for subjects having bilirubin levels from 0.2 to 0.7 mg/dL in men. When we stratified our analysis by smoking status, bilirubin consistently showed a protective effect on the risk of lung cancer on both never- and current smokers. Current smokers having bilirubin levels from 0.2 to 0.7 mg/dL had a risk of lung cancer by 6.0-fold higher than never-smokers with bilirubin levels ≥1.0 mg/dL in men. CONCLUSION: In this large prospective study, higher baseline bilirubin level in the normal range was associated with low risk of lung cancer. Smoking and low bilirubin levels were cumulatively associated with a higher risk of lung cancer.